Germany after the First World War - Bessel, Richard 1948- (Clarendon Press, 1993)
This is a social history of Germany in the years following the First World War. Germany's defeat and the subsequent demobilization of her armies had enormous economic, social, and psychological consequences for the nation, and it is these which Richard Bessel sets out to explore. Dr Bessel examines the changes brought by the War to Germany, by the return of the soldiers to civilian life and by the demobilization of the economy. He demonstrates how the postwar transition was viewed as a moral crusade by Germans desperately concerned about challenges to traditional authority; and he assesses the ways in which the experiences and memories of the War affected the politics of the Weimar Republic. This original and scholarly book offers important insights into the sense of dislocation, both personal and national, experienced by Germany and Germans after the First World War, and the damaging legacy of the War for German democracy.